TINJAUAN HUKUM ISLAM TERHADAP BUDAYA FOTO PRE-WEDDING (STUDI DI DESA TANJUNG BARU KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG) - Sumiati, Siti Aisah. Abu Bakar. (Fakultas Agama Islam, 2022)
Pre-wedding photos have become an inseparable part of one's wedding tradition. Pre-wedding photos are photos taken before the wedding ceremony. The purpose of pre-wedding photographers doing pre-wedding photos is to follow trends and as personal documentation. The research method used in this study is a qualitative research method, the type of field research. The location of this research was carried out in Tanjung Baru Village, Tanjung Morawa District, Deli Serdang Regency. The research subjects in this study were community leaders, religious leaders and pre-wedding photo takers. Data collection techniques used are observation, interviews and documentation. Pre-wedding photos taken by the people of Tanjung Baru Village were carried out before the marriage contract. Pre-wedding photos taken before the contract clearly violate Islamic law, such as ikhtilath (a mixture of men and women), khalwat (in taking photos together) and some even reveal their genitals (kasyiful aurot). Therefore, based on Islamic Shari'ah and ijtihad, scholars in Indonesia argue that the implementation of pre-wedding photos before the qabul consent is forbidden